2008
DOI: 10.1158/0008-5472.can-07-5031
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of ABT-737, a Selective Inhibitor of BCL-2, in Small Cell Lung Cancer

Abstract: Bcl-2 is a central regulator of cell survival that is overexpressed in the majority of small cell lung cancers (SCLC) and contributes to both malignant transformation and therapeutic resistance. We compared primary SCLC xenografts prepared from de novo human tumors with standard cell line-based xenografts in the evaluation of a novel and highly potent small molecule inhibitor of Bcl-2, ABT-737. ABT-737 induced dramatic regressions in tumors derived from some SCLC cell lines. In contrast, only one of three prim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 30 publications
5
151
0
Order By: Relevance
“…As a single agent ABT-737, a novel Bcl -2/ Bcl -xL inhibitor triggers apoptosis in various types of human cancers including multiple myeloma, leukemia, lymphoma and small cell lung cancer. [25][26][27][28][29] However, we [30][31][32] and others 33 have demonstrated that ABT-737 minimally inhibits cell growth in glioma when used as a single agent. The complexity of the interactions between cell surface receptors and downstream signaling targets has called into question the clinical utility of blocking any target in isolation, and the results of single agent-based strategies have to date been disappointing in patients with glioma.…”
Section: Introductionmentioning
confidence: 94%
“…As a single agent ABT-737, a novel Bcl -2/ Bcl -xL inhibitor triggers apoptosis in various types of human cancers including multiple myeloma, leukemia, lymphoma and small cell lung cancer. [25][26][27][28][29] However, we [30][31][32] and others 33 have demonstrated that ABT-737 minimally inhibits cell growth in glioma when used as a single agent. The complexity of the interactions between cell surface receptors and downstream signaling targets has called into question the clinical utility of blocking any target in isolation, and the results of single agent-based strategies have to date been disappointing in patients with glioma.…”
Section: Introductionmentioning
confidence: 94%
“…The clinical relevance of long-established SCLC cell lines is open to question (41), and SCLC patient-derived xenografts (PDX) have been demonstrated to better reflect the underwhelming clinical results seen with single-agent Navitoclax (42). To expand our results to a model that more accurately effects patients tumors, we assessed efficacy of GDC-0941 and Navitoclax in a SCLC CDX2 derived from circulating tumor cells (CTC) enriched prior to the donor patient's chemotherapy (30).…”
Section: Effect Of Combined Pi3k Inhibition and Bh3 Mimetic In Vivomentioning
confidence: 99%
“…However, there is considerable variation in the sensitivities of different SCLC cell lines to this drug (18,19). Studies in a variety of cell types have suggested that indicators of sensitivity include low levels of Mcl-1 and high levels of Bcl-2, Bcl-X L , Bim, and Noxa expression (19)(20)(21)(22)(23)(24)(25). In particular, studies in SCLC have documented that decreased Mcl-1 expression (19,20) and amplification of a region of chromosome 18 containing both the BCL-2 and NOXA genes correlates with increased sensitivity to ABT-737 (24).…”
Section: Introductionmentioning
confidence: 99%